ANALISIS KINERJA KEUANGAN DAERAH DAN KINERJA EKONOMI TERHADAP KESEJAHTERAAN MASYARAKAT DI PROVINSI NUSA TENGGARA BARAT: kinerja keuangan - wera hendri (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2020)
Prospirety of society was the form big problem and finished yet and we know that of prospirety prom the Human Development Index is conducted in different blooming between regency and provincy especially in NTB the West of Nusa Tenggara and differences arrising is caused there were differenced in organizer from each of teritory the potential of financial through fiscal desentralization and organizer of financial was an effective instrument to pushed prospirety of society life to goverment wanted but as we know that is till now occured pro and contra betweet some expert about the importance of function local financial performance and organizer of finncial to developed prospirety of society is still unconsistant or diffrent opinion from experts till now about the relation between variable to show signify the final relation that and it needed comprehensive model to determine of indication variable. So it coud solved the prospirety problem between regancy and prosvincy in the west of Nusa (NTB). The purposed of this research is analysed the effect of local financial performance in regency toward the performance of the area economy and prospirety of society especialy in regency area and provincy of Nusa (NTB) and the researched variable is used in this analysis were: the local financial performance, the performance of the area economy and prospirety of society. The data in this research is used the panel data. And the composite from ten Regency and provincy withtiming distace 2008 – 2017. And this data i got from Department of financial, and statistic center in west of Nusa (NTB) whereas tecnique of data is used by the PLS model. The conclusion from the product analysed were: (1) local financial performance was positif and significant influential toward the performance of the area economy; (2) local financial performance was positif and significant influential toward prospirety of society, (3) the performance of the area economy able with full mediation from local financial performance to prospirety of society